(untitled) (Medical Forum Monthly, 2026)
Objective: To assess impact of simulation of eye surgery skills on training of post graduate trainees at Dow University of Health Sciences. Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Simulation Laboratory of Dow University Health Sciences for a period of 3 months from 1st March 2025 to 30th May 2025. Methods: This study of 3 months duration after approval from institutional review board. Data regarding capsular rhexis and intracapsular maneuvers was taken from the Eyesi simulator system. Average score, minimum score, maximum score and total time taken were analyzed. They were then documented on and analyzed on SPSS version 25. Results: The data of 11 trainees was analyzed over a period of three months. The mean average score for Capsular rhexis was 86.13 with a standard deviation of 8.655. The mean of total time taken was 46.45 minutes with standard deviation of 14.955. Regarding intracapsular navigation the mean of total time was 19.90 minutes with a standard deviation of 6.53 The mean of average score was 75.7 with a standard deviation of 9.44. Conclusion: The individual scores of simulations showed that learning on it was a variable curve with improvement in the end.